Binder jet printed WC infiltrated with pre-made melt of WC and Co. (February 2020) - Cramer, Corson L.; Aguirre, Trevor G.; Wieber, Natalie R.; Lowden, Richard A.; Trofimov, Artem A.; Wang, Hsin; Yan, Jiaqiang; Paranthaman, M. Parans; Elliott, Amy M.
Abstract: WC-Co was made via binder jet additive manufacturing of tungsten carbide followed by melt infiltration with a Co-WC infiltrant. The goal of the study was to achieve fully densified parts in near-net shape with minimal shrinkage while keeping the Co content low. The exact amount of infiltrant was determined in order to fully densify with minimum shrinkage based on the actual volume taken up by WC powder in the preform based on theoretical density, the bounding volume of prints after shrinkage, and the volume from the infiltrant. The eutectic nature of the infiltrant enabled melting at much lower temperature compared to the melting temperature of pure Co. The density, microstructure, grain size, hardness, and fracture toughness were characterized. The shrinkage and net shaping were assessed with light scans. A detailed look at the fracture mechanics was assessed. This approach achieved highly dense WC-Co parts in net-shape with Co vol% of near 29 (Co wt% ~19), density of 96.2% theoretical, hardness of 8.34 GPa, grain size of 7.7 μm, magnetic saturation of 0.5 T, room temperature thermal conductivity of 125 W/mK, and fracture toughness of 24.7 MPa·m 1/2 . Highlights: WC was printed with binder jet additive manufacturing. WC prints were infiltrated with pre-made WC-Co. Eutectic point helped melt infiltrant at lower temperature. Excellent shape retention and Co wt% were achieved. Properties were comparable to traditional techniques.